Effectiveness of Online Physics Learning Platforms in Improving Students’ Learning Motivation - Kua, Maria Yuliana; Gelu, Afrianus; Kusairi, Sentot; Mogi, Theresia (Universitas Muhammadiyah Makassar, 2026)
This study explores ongoing motivation challenges in junior high school physics, where abstract concepts and teacher-centered methods often diminish student engagement. It aims to compare six online learning platforms Google Classroom, Canvas, Padlet, Nearpod, Genially, and Kahoot! in boosting students’ physics motivation using the ARCS framework (Attention, Relevance, Confidence, Satisfaction). A quasi-experimental, non-equivalent group pretest–posttest design was conducted across six junior high schools in Ngada Regency, Indonesia, involving 120 eighth-grade students (one intact class per school). Motivation was assessed with a validated 20-item ARCS-based questionnaire on a five-point Likert scale, complemented by classroom observations and teacher interviews for contextual insights. Data analysis included descriptive statistics, assumption tests (normality and homogeneity), paired-sample t-tests, one-way ANOVA, and Tukey HSD post hoc analysis. Results revealed significant increases in motivation from pretest to posttest for all platforms (p < 0.001), suggesting that platform-supported physics instruction can effectively boost student motivation. Notably, motivational improvements varied significantly across platforms (F = 9.400, p < 0.001): interactive and gamified platforms, especially Kahoot! and Nearpod, yielded higher gains than more text- and task-focused platforms such as Google Classroom and Padlet. The unique contribution of this study lies in its systematic comparison of multiple platforms within the same grade level and physics topic in a non-urban setting, interpreted explicitly through ARCS. The findings highlight that interactivity and immediate feedback are crucial for motivating students and offer evidence-based guidance for physics teachers and schools in choosing and integrating digital platforms to create more motivationally engaging instruction and professional development for technology-enhanced physics education.